Low prevalence of hemoperitoneum recurrence in dogs following splenectomy for benign splenic tumors - Fourthman, Brooke T.; Stewart, Samuel D.; Wilson-Robles, Heather; Khanna, Chand; Cawley, Jacob (Frontiers in Veterinary Science, 2025)
IntroductionThe purpose of this study is to describe the outcomes and prevalence of hemoperitoneum recurrence in dogs presumptively cured following splenectomy for spontaneously ruptured benign splenic lesions.MethodsA retrospective analysis of a cohort of 83 client-owned dogs with spontaneous hemoperitoneum due to a histologically benign, bleeding splenic lesion was performed. Medical records of dogs with ruptured benign splenic tumors presenting with hemoperitoneum were reviewed, in addition to owner follow-up, to determine if subsequent hemoperitoneum events occurred. Data were analyzed using statistical software(GraphPad Prism 10.1.2).ResultsA total of 59 patients (71%) were alive at the end of the follow-up period (median follow-up duration of 375 days; range: 128–1,062),with no new concerns related to previous splenectomy or hemoperitoneum. Of the 59 dogs, 6 died and 18 dogs (28.9%) were euthanized during the follow up period. Recurrent hemoperitoneum was identified in three dogs at 40, 68,and 385 days postoperatively, associated with a new liver lesion, an abdominal lesion of unclear origin, or hepatic nodules as the reason for the rebleeding events. Additional sectioning of the initial lesions was not performed.DiscussionSecond hemoperitoneum events occurred, but were uncommon, accounting for 3.6%of cases in this study. Reasons for recurrent spontaneous hemoperitoneum may include the development of a new lesion, the presence of a secondary non-splenic lesion that was unidentified during preoperative staging or abdominal exploratory, or histopathologic misdiagnosis of the original lesion.